Spatial Convergence in Major Dissolved Ion Concentrations and Implications of Headwater Mining for Downstream Water Quality. (10th January 2019) - Johnson, Brent; Smith, Elizabeth; Ackerman, Jerry W.; Dye, Susan; Polinsky, Robyn; Somerville, Eric; Decker, Chris; Little, Derek; Pond, Gregory J.; D'Amico, Ellen
Abstract: Spatial patterns in major dissolved solute concentrations were examined to better understand impact of surface coal mining in headwaters on downstream water chemistry. Sixty sites were sampled seasonally from 2012 to 2014 in an eastern Kentucky watershed. Watershed areas (WA) ranged from 1.6 to 400.5 km 2 and were mostly forested (58%–95%), but some drained as much as 31% surface mining. Measures of total dissolved solutes and most component ions were positively correlated with mining. Analytes showed strong convergent spatial patterns with high variability in headwaters (<15 km 2 WA) that stabilized downstream (WA > 75 km 2 ), indicating hydrologic mixing primarily controls downstream values. Mean headwater solute concentrations were a good predictor of downstream values, with % differences ranging from 0.55% (Na + ) to 28.78% (Mg 2+ ). In a mined scenario where all headwaters had impacts, downstream solute concentrations roughly doubled. Alternatively, if mining impacts to headwaters were minimized, downstream solute concentrations better approximated the 300 μS/cm conductivity criterion deemed protective of aquatic life. Temporal variability also had convergent spatial patterns and mined streams were less variable due to unnaturally stable hydrology. The highly conserved nature of dissolved solutes from mining activities and lack of viable treatment options suggest forested, unmined watersheds would provide dilution that would be protective of downstream aquatic life. Abstract : Research Impact Statement : Water chemistry, particularly many dissolved ions, changes little from headwater origins to downstream. Thus the chemistry observed at downstream sites represents the mix from all upstream activities.